IMPROVEMENT OF PREVENTION OF WOUND AND SYSTEMIC COMPLICATIONS DURING ALLOPLASTY OF STRENGTHENED POSTOPERATIVE VENTRAL HERNIAS - Isakov Pulatjon Mahmudzhonovich (Web of Journals Publishing, 2024)
Surgical treatment of postoperative hernias of the anterior abdominal wall at all times differed not only in the choice of the plasty method, but also in tactical approaches to preoperative preparation and examination of patients, intraoperative interpretation of the state of the hernia orifice, the method of the chosen hernioplasty, and therefore this problem remains relevant to this day. According to domestic and foreign authors, after performed laparotomies, in terms of 1 to 3 years, in more than 5% of cases, the development of postoperative hernias of the anterior abdominal wall is observed [1,5], and with recurrent hernias, up to 45% of cases [ 2.7].
Keywords: Postoperative ventral hernias (POVH), hernias of the anterior abdominal wall (APS), postoperative period.